Pengaruh Kepemimpinan dan Kompetensi Terhadap Pengembangan Sumber Daya Manusia Pada PT PLN (Persero) ULP Binjai Timur - Sinulingga, Putri Windari; Setiawan, Nashrudin (Universitas Negeri Medan, 2025)
The research analysis aims to determine whether leadership and competence have apositive and significant effect on human resource development at PT PLN (Persero) ULP Binjai Timur. The data analysis technique used is the quantitative associative research method with Structural Equation Modeling (SEM) analysis and using the SmartPLS application. This study usesmultiple linear regression. The sample in this study was 60 respondents. Primary data collection used a questionnaire. The results of the study indicate that leadership partially has a positive and significant effect on human resource development at PT PLN (Persero) ULP Binjai Timur. Competence partially has a positive and significant effect on human resource development at PTPLN (Persero) ULP Binjai Timur.